If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 8 = 8x + 56 Reorder the terms: 8 + 7x = 8x + 56 Reorder the terms: 8 + 7x = 56 + 8x Solving 8 + 7x = 56 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 8 + 7x + -8x = 56 + 8x + -8x Combine like terms: 7x + -8x = -1x 8 + -1x = 56 + 8x + -8x Combine like terms: 8x + -8x = 0 8 + -1x = 56 + 0 8 + -1x = 56 Add '-8' to each side of the equation. 8 + -8 + -1x = 56 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = 56 + -8 -1x = 56 + -8 Combine like terms: 56 + -8 = 48 -1x = 48 Divide each side by '-1'. x = -48 Simplifying x = -48
| 2x-8x=-20 | | 32=2/5(15p-10)p= | | 5(F-32)=-558.9 | | -6/7=1/2y-2/5 | | 5-(x/8)=10 | | X+5=12+2 | | 224=3(n-5) | | 3x+15=6x+21 | | 4n=9n-23 | | X=(y-6)/4 | | a-9=25 | | 7(1-x)=10-6(x+2) | | 4x-12=-4(7x+3)-7x | | 2.3x+1.2+2.5x=19.4-4.3x | | 1-4(u-1)=p | | 8x+12=12+8x | | 2(x+y)+y-6+10y= | | S-6=3-3 | | (4n-3)+(2n+5)= | | 0=x^5-6x^3+x | | 4(-4)-3y=-10 | | 6-6Z=-2(X+5) | | (79x-61y)(49x+5y)= | | 7a/10-3a/10 | | f(0)=1.25x | | 36/11=7/n | | 5(r+9)-5=p | | 0.3(d-100000)=202500 | | 2t+9=36 | | -4x+2x=8 | | 22=-4n+10 | | M-7=2-9 |